New Target Genes for the Peroxisome Proliferator-Activated Receptor-γ (PPARγ) Antitumour Activity: Perspectives from the Insulin Receptor - Daniela P. Foti; Francesco Paonessa; Eusebio Chiefari; Antonio Brunetti (PPAR Research)
The insulin receptor (IR) plays a crucial role in mediating the metabolic and proliferative functions triggered by the peptide hormone insulin. There is considerable evidence that abnormalities in both IR expression and function may account for malignant transformation and tumour progression in some human neoplasias, including breast cancer. PPARγ is a ligand-activated, nuclear hormone receptor implicated in many pleiotropic biological functions related to cell survival and proliferation. In the last decade, PPARγ agonists—besides their known action and clinical use as insulin sensitizers—have proved to display a wide range of antineoplastic effects in cells and tissues expressing PPARγ, leading to intensive preclinical research in oncology. PPARγ and activators affect tumours by different mechanisms, involving cell proliferation and differentiation, apoptosis, antiinflammatory, and antiangiogenic effects. We recently provided evidence that PPARγ and agonists inhibit IR by non canonical, DNA-independent mechanisms affecting IR gene transcription. We conclude that IR may be considered a new PPARγ “target” gene, supporting a potential use of PPARγ agonists as antiproliferative agents in selected neoplastic tissues that overexpress the IR.